DIFFERENCES IN TILs GRADE and PD-L1 EXPRESSION IN TNBC AND NON-TNBC AT PROF.DR.I.G.N.G. NGOERAH GENERAL HOSPITAL - Heryanto, Budi; Winarti, Ni Wayan; Saputra, Herman; Mahendra Dewi, I Gusti Ayu Sri; Mahastuti, Ni Made; Muliarta, I Made (E-Jurnal Medika Udayana; Vol 14 No 8 (2025): E-Jurnal Medika Udayana, 2025)
Breast carcinoma is type of cancer with high incidence and mortality rates in women worldwide. Breast carcinoma is divided into two categories, Invasive Breast Carcinoma of No Special Type (IBC-NST) and specific-type breast carcinoma. Breast carcinoma is divided into four surrogate molecular subtypes, Luminal A, Luminal B, HER2 overexpressive and TNBC. TIL s are mononuclear immune cells that infiltrate tumor tissue in breast carcinoma. PD-1 and its ligand PD-L1, are immune checkpoint inhibitors to regulate the body's immune response. The aim of study was to prove the difference in TIL s grade and PD-L1 expression between TNBC and non-TNBC.             This study was an observational analytic study with a cross-sectional study design. The study sample consisted of 42 IBC-NST patients who underwent biopsy/MRM and had histopathological and immunohistochemical (ER, PR, HER2, Ki67) examinations, comprising 21 non-TNBC patients and 21 TNBC patients at RSUP Prof.dr.I.G.N.G. Ngoerah, from January 1, 2021 to December 31, 2023. Analysis using chi-square showed a significant difference in TIL s grade and PD-L1 expression between TNBC and non-TNBC, with a p-value of 0.014 (p < 0.05) and a prevalence ratio (PR) of 1.58 (95% CI: 1.07 – 2.35).             In this study, the youngest age was 33 years old and the oldest was 76 years old, with an average age of 50.17±10.57 years. From the chi-square analysis, a statistically significant relationship was obtained between TNBC and non-TNBC with age (p<0.001), histological grade type (p=0.031), TIL s (p=0.014), and PD-L1 expression (p = 0.014).             In conclusion, there was a significant difference in the degree of TIL s and PD-L1 expression between patients with TNBC and non-TNBC at Prof.dr.I.G.N.G. Hospital. Ngoerah.   Keywords: invasive breast cancer, TIL s , PD-L1 expression.